Acidosis in arterial blood gas testing is associated with clinical outcomes after endovascular thrombectomy - Shao, Rui; Liu, Lei; Xu, Juan; Lan, Pengpeng; Wu, Guiping; Shi, Hongfeng; Li, Ruili; Zhuang, Yingle; Han, Shanshan; Li, Yan; Zhao, Ping; Xu, Min; et al. (Frontiers in Neurology, 2022)
Abstract Background: Despite recanalization, some of the patients undergoing endovascular thrombectomy (EVT) still suffer from unfavorable outcome. Patients with poor prognosis are often accompanied by acidosis in arterial blood gas (ABG) testing. We therefore explored the ABG testing results in the early phase of recanalization and analyzed their association with poor prognosis. Patients and methods: We identified all ischemic stroke patients with successful endovascular recanalization for anterior circulation vessel occlusion between June 2019 and May 2022. ABG testing was performed in all patients within 0-30min and 8 hours after endovascular therapy. We investigated the relationship between the ABG testing results with symptomatic intracerebral hemorrhage (sICH), hemicraniectomy and mortality. Results: A total of 123 stroke patients after endovascular thrombectomy were analyzed. Of those, 8(6.5%) patients had postinterventional sICH. Acidosis was associated with sICH. Decreased HCO3- levels and HCO3- levels at 8h after EVT were independently related with higher risk of sICH. 12 (9.8%) patients underwent hemicraniectomy for postischemic malignant edema and similar results were found for hemicraniectomy. Increased lactate at 8h after EVT and decreased HCO3- levels at 8h after EVT were closely associated with hemicraniectomy. 22 (17.9%) patients died within 3 months. Decreased HCO3- levels were independently related with mortality, as were decreased pH levels at 8h after EVT and decreased HCO3- levels at 8h after EVT. Conclusion: Acidosis is associated with clinical outcomes after endovascular therapy and may help to select patients with poor prognosis in the acute early phase of recanalization.